Egg reappearance periods of anthelmintics against equine cyathostomins: The state of play revisited. (April 2023) - Macdonald, Stephanie L.; Abbas, Ghazanfar; Ghafar, Abdul; Gauci, Charles G.; Bauquier, Jenni; El-Hage, Charles; Tennent-Brown, Brett; Wilkes, Edwina J.A.; Beasley, Anne; Jacobson, Caroline; Cudmore, Lucy; Carrigan, Peter; et al.
Abstract: Cyathostomins are the most common and highly prevalent parasites of horses worldwide. Historically, the control of cyathostomins has mainly relied on the routine use of anthelmintic products. Increasing reports on anthelmintic resistance (AR) in cyathostomins are concerning. A potential method proposed for detecting emerging AR in cyathostomins has been estimating the egg reappearance period (ERP). This paper reviews the data available for the ERP of cyathostomins against the three major classes of anthelmintics, macrocyclic lactones, tetrahydropyrimidines, and benzimidazoles. Published peer-reviewed original research articles were obtained from three databases (PubMed, CAB Direct and Web of Science) and were evaluated for their inclusion in a systematic review. Subsets of articles were then subjected to a review of ERP data. A total of 54 (of 134) studies published between 1972 and 2022 met the criteria for inclusion in the systematic review. Until the beginning of 2022, there was no agreed definition of the ERP; eight definitions of ERP were identified in the literature, complicating the comparison between studies. Additionally, potential risk factors for the shortening of the ERP, including previous anthelmintic use and climate, were frequently not described. Reports of shortened ERP for moxidectin and ivermectin are frequent: 20 studies that used comparable ERP definitions reported shortened moxidectin and ivermectin ERPs of 35 and 28 days, respectively. It is unclear whether the ERPs of these anthelmintics reduced to such levels are due to the development of AR or some biological factors related to horses, cyathostomin species, and/or the environment. The ERPs for other anthelmintics, such as fenbendazole and pyrantel, were frequently not reported due to established resistance against these drugs. Future research in horses is required to understand the mechanism(s) behind the shortening of ERP for cyathostomins. Based on this systematic review, we propose recommendations for future ERP studies. Graphical abstract: Image 1 Highlights: Is the egg reappearance period (ERP) an early indicator of anthelmintic resistance? A summary of cyathostomins ERP for equine registered anthelmintics from 1972 to 2022. Recent developments on the definition of ERP. Proposed recommendations for future ERP studies.